IMPROVING THE CHARACTER OF STUDENT COOPERATION THROUGH THE IMPLEMENTATION OF P5 CLASS V - Nurdin Kamil; Esti Susiloningsih; Magdalena Vianty; Zona Anggraini; Vinencia Ika Indralin (Jurnal Cakrawala Pendas, 2025)
This research aims to improve the character of student cooperation through the implementation of Project-Based Learning on the topic of Indonesian cultural diversity in grade V of SDN 112 Palembang. The background of the research is based on the low cooperative skills of students as seen from the lack of active participation, communication, and responsibility in group activities. This research is a Class Action Research (PTK) which is carried out in two cycles, each consisting of planning, implementation, observation, and reflection stages. In the first cycle, most of the students have not shown optimal cooperation character. However, after improvements were made in cycle II with an emphasis on role sharing, intensive guidance, and the use of lighter media, there was a significant increase. The results of observations in the second cycle showed that 20 students (76.9%) were in the good cooperation category, 5 students (19.2%) in the medium category, and only 1 student (3.9%) in the low category. These results are in line with several previous studies that state that the Project-Based Learning approach is effective in fostering students' collaborative skills and character. Thus, project-based learning can be used as an alternative learning strategy to build the character of student cooperation holistically.